pengaruh dimensi easy to use dan efficiency terhadap customer satisfaction pengguna aplikasi bni mobile banking di kota yogyakarta - Ahmad Faturohman (Program Studi Manajemen Fakultas Ekonomi UST, 2019)
This study aims to determine the effect of easy to use, efficiency and customer satisfaction. Samples were taken as many as 50 respondents using accidental sampling method. Analysis method is with data collection is done by distributing questionnaires using a 1-5 point scale to measure 10 question indicators. Data analysis used validity and reliability test, classic assumption test. Only after that is done a multiple linear regression test. The results of this study indicate the easy to use variable has an effect on customer satisfaction. Keywords: Easy to Use, Efficiency and Customer Satisfaction.